CLINICAL AND ECONOMIC EVALUATION OF THROMBOPOIETIN RECEPTOR AGONISTS IN THE TREATMENT OF CHRONIC IDIOPATHIC THROMBOCYTOPENIC PURPURA IN ADULTS - E. A. Pyadushkina; M. Yu. Frolov; M. V. Avksentyeva (Фармакоэкономика, 2016)
Aim. Hospital-based economic analysis for the use of thrombopoietin receptor agonists (TRA) Eltrombopag and Romiplostim has been performed in patients with chronic idiopathic thrombocytopenic purpura (ITP) at the background failure of previous treatment options. Materials and methods. Two models for the cost-minimization analysis (model 1) and analysis of the budget impact TRA usage (model 2) are developed on the basis of Microsoft Excel software. The models are based on hypothesis of the difference between the drugs in terms of clinical efficacy and safety and this hypothesis is grounded on the results of randomized controlled trials (RCT) and indirect RCT comparison. The expenditures for drugs of TRA group and for the medical care including the costs for drugs administration, bleeding treatment, "rescue therapy" and follow-up monitoring during treatment are calculated in the mentioned models. The costs of the RF health system have been calculated taking into account the management peculiarities and financing of medical assistance that allows use the models in all regions of Russia. The study was conducted from September to December 2015. The data of state statistical supervision, registered limit transfer drug prices from the list of life-saving and essential medicines (LSEM), the guide price of the manufacturer in the case of application filing for Eltrombopag inclusion to such list, and standards of the financial expenses per medical care volume unit of RF in 2015 are used for calculations. Results. It was shown that Eltrombopag use as compared to Romiplostim is economically expedient in the patients with chronic ITP at the background of previous treatment failure, being not less effective and cheaper alternative that allows reduce the cost of one patient annual therapy by 2.68 mln. rubles. Budget impact analysis evidences that Eltrombopag application can significantly reduce the spending of budgetary funds for the chronic ITP therapy, at least with the same efficacy. Budgetary spending is decreased by 1.68 bln. rubles over 5 years with a gradual increase of Eltrombopag share in purchase of TRA. Conclusion. Despite the comparable efficacy and safety Eltrombopag is economically sound option of chronic ITP treatment as compared to Romiplostim.